2011
DOI: 10.3389/fpsyg.2011.00015
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating Objects and Telling Words: A Study on Concrete and Abstract Words Acquisition

Abstract: Four experiments (E1–E2–E3–E4) investigated whether different acquisition modalities lead to the emergence of differences typically found between concrete and abstract words, as argued by the words as tools (WAT) proposal. To mimic the acquisition of concrete and abstract concepts, participants either manipulated novel objects or observed groups of objects interacting in novel ways (Training 1). In TEST 1 participants decided whether two elements belonged to the same category. Later they read the category labe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 35 publications
4
83
0
1
Order By: Relevance
“…When a child obtains language, the meaning of an abstract word has to be explained linguistically. This would be a bodily experience as well which might lead to face-related motor activity during abstract word processing (Borghi, Flumini, Cimatti, Marocco, & Scorolli, 2011;Scorolli et al, 2012). This research group also reports arm-related sensorimotor activity during abstract word processing in a later postlexical stage (Scorolli et al, 2012).…”
Section: Sensorimotor Involvement In Non-action Verb Processingmentioning
confidence: 94%
“…When a child obtains language, the meaning of an abstract word has to be explained linguistically. This would be a bodily experience as well which might lead to face-related motor activity during abstract word processing (Borghi, Flumini, Cimatti, Marocco, & Scorolli, 2011;Scorolli et al, 2012). This research group also reports arm-related sensorimotor activity during abstract word processing in a later postlexical stage (Scorolli et al, 2012).…”
Section: Sensorimotor Involvement In Non-action Verb Processingmentioning
confidence: 94%
“…Several authors have emphasized the role of affective and social experiences in abstract concept acquisition and embodiment (Borghi, Flumini, Cimatti, Marocco, & Scorolli, 2011;Kousta, Vigliocco, Vinson, Andrews, & Del Campo, 2011;Vigliocco, Meteyard, Andrews, & Kousta, 2009;Wiemer-Hastings & Xu, 2005;Zdrazilova & Pexman, 2013). Crutch et al (Crutch, Williams, Ridgway, & Borgenicht, 2012) obtained ratings for 200 abstract and 200 concrete nouns on the relatedness of each word to concepts of time, space, quantity, emotion, polarity (positive or negative), social interaction, morality, and thought, in addition to the more physical dimensions of sensation and action.…”
Section: Introductionmentioning
confidence: 99%
“…While most of the previous studies in grounding focused on representations of concrete words, objects and action, recent studies have begun to provide evidence to demonstrate the grounding of abstract concepts, for example, grounding time in the representation of space (Flusberg, Thibodeau, Sternberg, & Glick, 2010). Borghi, Flumini, Cimatti, Marocco, and Scorolli (2011) suggested that even though abstract concepts are not grounded on a single concrete object, they can be grounded on relationships between different objects. It should be noted that the grounded view of cognition particularly emphasizes that cognitive processes can be grounded in many ways such as simulations, situated action and bodily states, and the involvement of the body is not always necessary, which seems to differ from the general idea of "embodied" cognition (Barsalou, 2008(Barsalou, , 2010.…”
Section: Main Streams Of Embodied Cognition Researchmentioning
confidence: 99%